The Importance of the Admissibility of Evidence in Lithuanian Civil Procedure - Bartkus, Jurgis (Teisė, 2021)
The article analyses the importance of the admissibility of evidence in Lithuanian civil proceedings. The analysis of various sources of law allows to link the admissibility of evidence in civil proceedings not only with one of the features of evidence, but also with the objectives of this institute in civil proceedings: ensuring the quality of proof, the cost-efficient process, a fair and just trial, and other values. The reduction of the importance of the admissibility of evidence is essentially influenced by aspects related to the whole evidentiary process – the principle of free evaluation of evidence, the purpose of determination of material truth, and procedural norms establishing the judge as the final assessor of admissibility of evidence and facts. The objectives of the admissibility of evidence in civil proceedings make it necessary to find possible solutions that ensure a more appropriate relationship between the admissibility of evidence and the reasons of its importance.